Relationship between apnoea-hypopnoea index and angiographic coronary disease phenotypes in patients presenting with acute myocardial infarction. (June 2013) - Hein, Thet; Loo, Germaine; Ng, Wai-Yee; Tai, Bee-Choo; Kajiya, Takashi; Tan, Adeline; Khoo, See-Meng; Chan, Mark; Low, Adrian F.; Chia, Boon-Lock; Richards, Mark; Lee, Chi-Hang
Abstract Background: Relationship between obstructive sleep apnoea and atherosclerosis has not been confirmed using coronary angiography. We sought to investigate the relationships between the apnoea-hypopnoea index (AHI) and angiographic coronary disease phenotypes. Methods: SYNTAX score, lesion complexity, and thrombus burden grade were determined in 125 patients presenting with acute myocardial infarction and had undergone a screening sleep study. Severe OSA was defined as AHI ≥ 30. Results: Most of the recruited patients were male (97.6%). Severe obstructive sleep apnoea was diagnosed in 37% of the patients. The severe obstructive sleep apnoea group (n = 46) was older (P = 0.039) and more obese (P = 0.003) than the non-severe group (n = 79). There was no evidence of difference between the severe and non-severe obstructive sleep apnoea groups with regard to SYNTAX score (P = 0.871), number of complex lesions (P = 0.241), and thrombus burden grade (P = 0.433). Multivariate analysis adjusting for difference in age and body mass index did not change the findings. Conclusion: Using the three angiographic scoring systems, we found no association between AHI and angiographic coronary disease phenotypes, suggesting a limited effect of obstructive sleep apnoea on the amount and distribution of coronary plaques in patients presenting with acute myocardial infarction.